NNBI for ITER: status of long pulses in deuterium at the test facilities BATMAN Upgrade and ELISE. (11th August 2021) - Wünderlich, D.; Wimmer, C.; Riedl, R.; Bonomo, F.; Fröschle, M.; Mario, I.; Mimo, A.; Yordanov, D.; Fantz, U.; Heinemann, B.
Abstract: For the D-T operational phase of the international fusion experiment ITER, starting in 2035, pulses are planned with Q > 10 and a duration of 400 s and pulses with Q = 5 for up to 3600 s. The two neutral beam injection (NBI) systems will deliver 33.3 MW of heating power to the plasma and will also be an important source for non-inductive current drive. An essential part of the NBI systems is a large RF driven source for negative hydrogen or deuterium ions. In order to fulfil the requirements imposed to the NBI system, the ion source has to deliver an intense, stable and homogeneous large negative ion beam over pulse lengths of 400 s or 3600 s. Till now, long pulses in deuterium at the extracted negative ion current density required for ITER could not be demonstrated. The achievable performance is limited by a high current and a pronounced vertical asymmetry of the co-extracted electrons, both strongly increasing with time, whereas the stability of the negative deuterium ions is not an issue. For reduced performance, i.e. reduced negative ion current, lower and more stable co-extracted electron currents are observed, making possible pulses up to 3600 s (using pulsed extraction). One main aim of ongoing investigations at the two test facilities BATMAN Upgrade (Bavarian test machine for negative ions) and ELISE (extraction from a large ion source experiment) is the development of scenarios stabilizing and symmetrizing the co-extracted electron current in deuterium. These investigations are discussed and the current status of hardware upgrades ongoing at BATMAN Upgrade and ELISE towards the ITER scenario of one-hour steady state extraction is presented.